The 36 dramatic situations - Figgis, Mike 1948- (Faber & Faber, 2017)
"All drama takes the form of one of 36 situations. That was Georges Polti's theory about theatre, which he put forward in his book The Thirty-Six Dramatic Situations, published in French in the mid-19th century. a century and a half later, Mike Figgis was struggling with a film treatment. He couldn't get it right. But when he turned to Polti's book, the sample situations helped clarify his ideas and broaden the landscape of his creativity. He saw just how useful this sort of framework could be for writers, and decided to rework Polti's theory for a modern, film-focused audience. Combining re-imagined situations with cinematic examples, and chart-based analysis of 150 great films, the resulting book is an invaluable a stimulating tool for any writer."--Page 4 of cover
Keywords: Film; Polti, Georges / 1868- / Themes, motives / Criticism and interpretation; Motion pictures / Plots, themes, etc; Plots (Drama, novel, etc.); Drama / Technique